Characteristics of Residual Symptoms After Laminoplasty in Diabetic Patients With Cervical Spondylotic Myelopathy: A Prospective Cohort Study. Issue 12 (15th June 2017) - Machino, Masaaki; Imagama, Shiro; Ando, Kei; Kobayashi, Kazuyoshi; Hida, Tetsuro; Ito, Kenyu; Tsushima, Mikito; Matsumoto, Akiyuki; Tanaka, Satoshi; Morozumi, Masayoshi; Ito, Keigo; Kato, Fumihiko; et al.
Abstract : Study Design: A prospective cohort study. Objective: The purpose of this study was to compare cervical laminoplasty outcomes between diabetic and nondiabetic patients with cervical spondylotic myelopathy (CSM), and to characterize residual symptoms of diabetic patients. Summary of Background Data: Diabetes is one of the most frequent comorbidities in CSM patients. However, no report has elucidated residual symptoms following surgery in diabetic patients with CSM. Methods: A total of 505 consecutive patients with CSM (331 males, 189 females; mean age, 66.6 years; age range, 41–91 years; >1-year follow up after laminoplasty) were enrolled and divided into diabetic group (n = 105) and nondiabetic group (n = 400). The Japanese Orthopedic Association (JOA) scores and recovery rate (RR) of each function were compared between the groups. To quantitatively assess performance, the 10-s grip and release (G&R) test and the 10-s step test were evaluated. Results: There was no significant difference in the mean RRs of upper extremity motor function between diabetic and nondiabetic patients (59.2% vs. 60.5%, respectively; P = 0.789). The RR of lower extremity motor function was lower in the diabetic group than in the nondiabetic group (36.1% vs. 43.4%, respectively; P = 0.047); the RR of upper extremity sensory function also was lower (36.8% vs. 49.6%, respectively; P = 0.006). However, the mean RRs of sensory functions of lower extremities were 59.7% (diabetic) and 59.2% (nondiabetic) ( P = 0.953). There was no significant difference in the mean RRs of trunk sensory function between the groups (69.3% vs. 74.1%, respectively; P = 0.303). The mean RRs of urinary bladder function were 42.1% (diabetic) and 53.7% (nondiabetic) ( P = 0.035). The preoperative mean number of the 10-s step test was lower in the diabetic group than in the nondiabetic group, and the postoperative mean number also was significantly lower in the diabetic group. Conclusion: Gait disturbance, hand numbness, and bladder dysfunction after surgery persisted more than other symptoms in the diabetic than in the nondiabetic patients. Level of Evidence: 2